Room Temperature Ferromagnetism Observed in Co-doped LaTiO3 Nanofibers Fabricated by Electrospinning and Calcination - Wichaid Ponhan (Science Faculty of Chiang Mai University, 2019)
In this study, LaTi1-xCoxO3 nanofibers with x = 0, 0.025, 0.05, 0.075 and 0.1 were fabricated by electrospinning technique and calcination. The LaTi1-xCoxO3 nanofibers with average diameters of ~ 135 - 186 nm were successfully obtained from calcination of the as-spun LaTi1-xCoxO3/PVP nanofibers at 1000 ฐC in argon for 2 h. The calcined LaTi1-xCoxO3 nanofibers were characterized by a variety of techniques. X-ray diffraction and transmission electron microscopy studies indicated all samples calcined at 1000 ฐC are a single phase of cubic perovskite structure with no secondary magnetic phase in this study. All of the samples with x = 0, 0.025, 0.05, 0.075 and 0.1 are found to be ferromagnetic at room temperature. With the increasing of x, the ferromagnetism was increased. The structural defect such as oxygen vacancies may play an important role to induce room temperature ferromagnetism in LaTi1-xCoxO3 nanofibers.